(untitled) (American Journal of Islam and Society, 2010)
This article analyzes the Muslim Pangal community of Manipur in northeastern India. Although its members have been fairly integrated with other groups, their liberal cultural sense, infused with a deep religious grounding, has allowed them to borrow various cultural traits, including language. Apart from Islam, their cultural whole is based on, among other elements, language, dressing patterns, social arrangements, folk songs, and courtship rituals.